Perbandingan Tingkatan Mujtahid dalam Empat Mazhab: Ushul Fikih dan Kontekstualisasi Ijtihad - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study examines the hierarchical classification of mujtahid within the four Sunni schools through a comparative ushul al-fiqh perspective, emphasizing its relevance for the contextualization of ijtihad. It highlights levels such as mujtahid mutlaq, mujtahid mazhab, mujtahid tarjīḥ, and mujtahid fatwa, which reflect varying degrees of authority and competence in legal reasoning. While Hanafi and Maliki approaches demonstrate greater flexibility and contextual adaptation, Shafi‘i and Hanbali traditions emphasize methodological rigor and textual discipline. The study argues that this hierarchy enables continuity and innovation in Islamic law. In contemporary settings, activating these levels supports adaptive, methodologically grounded, and context-sensitive legal responses. Keywords: Mujtahid Levels, Ijtihad, Ushul al-Fiqh